MENSTIMULASI KETERAMPILAN SOSIAL ANAK USIA DINI MELALUI SENI PERMAINAN TRADISIONAL - Zakiya, Zakiya; Mayar, Farida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
The age development influences children's play. Children prefer online games and gadgets. The inherent impression of the use of gadgets by children today is being addicted to playing online games. This negative impact should make observers, educators and researchers more sensitive in introducing various forms of games that have existed for generations, such as traditional games. This study aims to identify games that are able to stimulate children's social skills in their early childhood. The research method in this paper is library research or library research. Some of these traditional games must be introduced to children to stimulate children's social skills.